Processos de ensino-aprendizagem em Educação das relações étnico-raciais: interface didático-curricular - Targino, Fábio (2019)
The universe of teaching practice is a field of possibilities for the debate on the development of the curriculum and the teaching-learning processes in the Education of Ethnic-Racial Relations (EERR), focusing on the black population. Our concern is in the geopolitical conjuncture of the twenty-first century, characterized by globalization and its contradictions, such as xenophobia and racism, evidenced in conflicts especially against black populations by those who conceive a monocultural society. These conflicts have direct implications in the construction of social exclusion societies, as in the case of Brazil, where the racial dimension is an explanatory element of the situations of vulnerability to which black populations are exposed in the country. Understanding the strategic role of school education as a right and a condition to face ways of prejudice and discrimination against blacks, we ask ourselves how do we develop didactic-curricular strategies mobilized by Basic Education teachers to promote processes of teaching-learning oriented to the Education of Ethnic-Racial Relations that consider the issues arranged in Law 10.639 / 03. In order to reach the objective of answering this question, which is the main topic of reflections that are focused in this study, we have specific objectives: characterize didactic-curricular strategies for the EERR practiced by teachers of Basic Education ; Understand the meanings attributed by teachers to EERR themes; Identify didactic challenges for curriculum development for the EERR. In the context of the Brazilian school, since the promulgation of Law 10.639 / 03, there is an effort to consolidate educational projects that promote the overcoming of structurally culturalized racism in Brazilian society through the curricular recognition of Afro-Brazilian cultural knowledge. The theoretical framework used in the research includes contributions from the didactic-curricular debate, such as Arroyo (2013), Sacristán (2010, 2013), Silva (2017) and Candau (2003, 2007, 2008, 2012, 2013); and the debate about ethnic-racial relations, for example, Gomes (2013), Nascimento (2002) and Macedo (2016). The methodology consisted of an exploratory design, of quantitative and qualitative character, in the search to reveal, in the reports and conceptions of teachers accessed through a virtual questionnaire, the relation between EERR conceptions of teachers of Basic Education and structed teaching-learning processes from didactic and curricular strategies to promote the appreciation of the Afro-Brazilian culture. The research had the participation of 66 teachers of basic education, who answered a questionnaire composed of 23 questions (closed and multiple choice) about practices developed in the theme of EERR and its attributions based on Law 10.639 / 03. At the end of this dissertation it is concluded that, although Law 10.639 demands a new didactic-curricular formulation that values the contribution of the black people in the History and Culture of Brazilian society, the implementation of the Law by itself does not guarantee the necessary changes, with regard to EERR in the school environment, further when teachers do not get adequate training to work on the subject, a problem that is characterized as one of the main challenges of EERR, even after the 16 years of consolidation of the Law.